PENGEMBANGAN MEDIA PEMBELAJARAN MOBILE LEARNING BERBASIS ANDROID PADA MATERI INVERTEBRATA UNTUK SISWA KELAS X SMA - Gunanto, Prio Eko; Sujarwanta, Agus; Widowati, Hening (Lembaga Penelitian UM Metro, 2019)
Teaching and learning activities in class require learning media that are able to convey material messages well. Learning media can be made by utilizing information technology, namely in the form of android-based learning media mobile learning. This research aims to (1) produce android-based mobile learing learning media in high school class X Invertebrate material that is good and worthy of being used as a learning media. (2) find out the response of users of mobile learning media, namely high school class X students to the learning media developed. This type of research is development research. Learning media developed using a development model proposed by Thiagarajan. The subjects of this study were 3 expert lecturers, 10 students in the limited trial and 20 students in the field trial. From the results of the study, product validity is in very good and valid criteria with a score of 83.64% in design aspects, 100% in material aspects, 93% in IT aspects, 83.33% in limited trials, 85.10% in field trials. This mobile learning media learning product is considered valid and feasible to be used to support biology learning activities.